2008
DOI: 10.1097/01.tp.0000332216.29105.ab
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the Diagnosis of Chronic Antibody Mediated Rejection: Loss of Peritubular Capillaries, Wide Spectrum, and Transient Nature of C4d Deposition

Abstract: To compare the renal function, safety and effi cacy parameters in everolimus vs MMF group with cyclosporine at 1 year. This is a prospective non randomized open label study in denovo live related renal transplant recipients. Total 60 patients above 18years and fi rst renal transplant were included in the study (30 in each arm). CsA was started on day -2 with 8 mg/kg/day in both groups and tapered to achieve C2 level of 1-1.4 ƒÝgm/ml vs 1.7 ƒÝgm/ml at 1month and 0.55 ¡V 0.65 ƒÝgm/ml vs 1.2 ƒÝgm/ml at 3 month an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It is clear that at least some of the C4dϪ glomerulopathies are the residue of prior C4dϩ episodes. We have seen C4dϪ transplant glomerulopathy cases that had prior episodes of acute humoral rejection or CHR [27]. Other C4dϪ glomerulopathy cases in our experience are part of a pattern of thrombotic microangiopathy.…”
Section: Association With Circulating Dsamentioning
confidence: 65%
See 1 more Smart Citation
“…It is clear that at least some of the C4dϪ glomerulopathies are the residue of prior C4dϩ episodes. We have seen C4dϪ transplant glomerulopathy cases that had prior episodes of acute humoral rejection or CHR [27]. Other C4dϪ glomerulopathy cases in our experience are part of a pattern of thrombotic microangiopathy.…”
Section: Association With Circulating Dsamentioning
confidence: 65%
“…Quantitative studies showed that 43% of the CD34ϩ capillaries were C4dϩ, and the range was 1-89%, with no clear threshold [27]. This is in contrast to acute humoral rejection in which Ͼ50% of the capillaries are usually C4dϩ and indeed Ͼ50% positive capillaries is generally taken as the diagnostic threshold.…”
Section: Transplant Capillariopathymentioning
confidence: 90%
“…27 In any case, loss of PTCs can affect the extent of C4d positivity and contribute to the lower density of C4d + PTCs often observed in CHR. 28 One difficulty in the recognition of CHR is that not all diagnostic components may be present at any particular time.…”
Section: Chrmentioning
confidence: 99%
“…We have seen several instances in which previous or subsequent biopsy results of patients with transplant glomerulopathy and C4d+ showed glomerulopathy and no C4d deposition. 28 It is also possible that those cases with transplant glomerulopathy and DSA but without C4d are due to complement-independent antibody-mediated injury.…”
Section: Chrmentioning
confidence: 99%
“…This could happen when the DSAs induce damage via a non-complement fixing mechanism (Collins et al, 2008). Further, in advanced stages of CAMR, when tubular atrophy has already developed, it may well be hard to recognize positive C4d staining.…”
Section: T-cell Mediated Rejectionmentioning
confidence: 99%